Robotic-Assisted Transperitoneal Aortic Lymphadenectomy as Part of Staging Procedure for Gynaecological Malignancies: Single Institution Experience - V. Zanagnolo; D. Rollo; T. Tomaselli; P. G. Rosenberg; L. Bocciolone; F. Landoni; G. Aletti; M. Peiretti; F. Sanguineti; A. Maggioni (Obstetrics and Gynecology International)
Introduction. This study was designed to confirm the feasibility and safety of robotic-assisted transperitoneal aortic lymphadenectomy as part of staging procedure for gynecologic malignancies. Methods. Chart review of 51 patients who had undergone robotic staging with aortic lymphadenectomy for different gynaecologic malignancies was performed. Results. The primary diagnosis was as follows: 6 cases of endometrial cancer, 31 epithelial ovarian cancer, 9 nonepithelial ovarian cancer, 4 tubal cancer, and 1 cervical cancer. Median BMI was 23 kg/m2. Except for a single case of aortic lymphadenectomy only, both aortic and pelvic lymphadenectomies were performed at the time of the staging procedure. All the para-aortic lymphadenectomies were carried out to the level of the renal veinl but 6 cases were carried out to the level of the inferior mesenteric artery. Hysterectomy was performed in 24 patiens (47%). There was no conversion to LPT. The median console time was 285 (range 195–402) with a significant difference between patients who underwent hysterectomy and those who did not. The median estimated blood loss was 50 mL (range 20–200). The mean number of removed nodes was 29±9.6. The mean number of pelvic nodes was 15±7.6, whereas the mean number of para-aortic nodes was 14±6.6. Conclusions. Robotic transperitoneal infrarenal aortic lymphadenectomy as part of staging procedure is feasible and can be safely performed. Additional trocars are needed when pelvic surgery is also performed.